2016
DOI: 10.1002/adfm.201603223
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Liquid Marbles: Controlling Structure, Shape, Stability, and Motion

Abstract: Liquid marbles" are liquid-in-gas dispersed systems stabilized by hydrophobic solid particles adsorbed at the gas-liquid interface. The structure, stability and movement of these liquid marbles can be controlled by external stimuli such as pH, temperature, light, magnetic and electric fi elds, ultrasonic, mechanical stress and organic solvents. Stimuli-responsive modes can be categorized into fi ve classes: (i) liquid marbles whose stability can be controlled by adsorption/desorption of solid particles to/from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
156
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 154 publications
(219 reference statements)
0
156
0
Order By: Relevance
“…This is why it is difficult to measure contact angle hysteresis on MOF powders. The advancing contact angle can be measured with reasonable accuracy by increasing the droplet volume, but the removal of liquid to measure the receding contact angle can cause the droplet to pick up powder grains, which strongly influences the measurement and may lead to the formation of a “liquid marble.” Therefore, it is inadvisable to measure contact angle hysteresis on powders; such measurements should ideally only be performed on pressed pellet disks.…”
Section: Synthesis Of Hydrophobic Mof Materialsmentioning
confidence: 99%
“…This is why it is difficult to measure contact angle hysteresis on MOF powders. The advancing contact angle can be measured with reasonable accuracy by increasing the droplet volume, but the removal of liquid to measure the receding contact angle can cause the droplet to pick up powder grains, which strongly influences the measurement and may lead to the formation of a “liquid marble.” Therefore, it is inadvisable to measure contact angle hysteresis on powders; such measurements should ideally only be performed on pressed pellet disks.…”
Section: Synthesis Of Hydrophobic Mof Materialsmentioning
confidence: 99%
“…[21] The lifetime is related to many aspects, like particles size, surface chemistry, and the external conditions. [21][22][23] The manipulation of single LMs, by the mechanical force, [24,25] magnetic locomotion [26][27][28] and light-driven motivation [29,30] have been developed in the past decade. Benefiting from the single LM manipulation and liquid control, the coalescence of the well-prepared LMs can mix the Coalescence and splitting of liquid marbles (LMs) are critical for the mixture of precise amount precursors and removal of the wastes in the microliter range.…”
mentioning
confidence: 99%
“…Destabilization of the bubbles prepared at pH ~10 could be induced by subsequent pH adjustment to ≤ 3.0, and the stabilization/destabilization cycles were reversible. Recently, it has been confirmed that there are lots of similarities among particle-stabilized bubbles, emulsions and liquid marbles/dry liquids (Fujii et al, 2016). The principles demonstrated in this study should also be applicable to predict the stabilities and microstructures of these particle-stabilized soft dispersed systems.…”
Section: Resultsmentioning
confidence: 98%